Parental resistance : mobile and transitory discourses : a discursive analysis of parental resistance towards medical treatment for a seriously ill child : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Nursing, Massey University, Palmerston North, New Zealand - Woods, Martin (Massey University, 2007)
This qualitative thesis uses discourse analysis to examine parental resistance towards medical treatment of critically ill children. It is an investigation of the 'mobile and transitory' discourses at play in instances of resistance between parents, physicians and nurses within health care institutions, and an examination of the consequences of resistance through providing alternative ways of perceiving and therefore understanding these disagreements. The philosophical perspectives, methodology and methods used in this thesis are underpinned by selected ideas taken from the works of Michel Foucault and Pierre Bourdieu and supported by relevant literature in the fields of media, law, children, parenting, caring, serious childhood illness, medicine and nursing. The thesis obtains information from a variety of texts that includes established literature (such as medical, sociological, legal, academic and philosophical), newspaper articles, radio or television interviews, internet sources, court reports and proceedings, legal experts and other commentators - and 15 interview based texts, where the focus is on analyses of narratives of parents, doctors and nurses. In the texts gathered for this thesis, there are noticeable differences between the personal experience discourses of parents, the 'in-between' discourses of nurses, and the disciplined discourses of physicians. This thesis brings these discourses into conversation with each other suggesting that parental resistance does not occur because of an infrequent and unusual set of circumstances where a few socially isolated and/or 'difficult' parents disagree with the treatment desires of paediatric physicians. Instead, it is argued that from an examination of interview based texts, parental resistance is an omnipresent but transitory occurrence that affects many of the interactions between the parents of seriously ill children and clinical staff. It is maintained that within these interactions, the seeds of this resistance are sown in both critical decision making situations and in everyday occurrences between doctors, nurses and parents within healthcare institutions. Contributing factors to parental resistance include the use of power games by staff, the language of medicine, forms of symbolic violence, the presence or absence of trust between parents and medical staff, the effects of medical habitus, and challenges to the parental role and identity. Overall, it is proposed in this thesis that parents who resist treatment for their seriously ill child are not exceptions to the normative patient-physician relationship. Instead an analysis of their discourses and practices is able to illuminate the complex interactions between patients and medical conventions. It is therefore possible to see parents who resist medical advice not as peripheral to the medical encounter but as examples of how patient-physician relationships come to be codified, constructed and crafted through everyday discourses and practices within health care settings.
Keywords: Parent-medical staff interaction; Parent attitudes; Child health care; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services::321299 Public health and health services not elsewhere classified